Monarchical Constitutional Guardianship and Legal Métissage in Asia. Issue 3 (24th October 2022) - De Visser, Maartje; Harding, Andrew
Abstract: This article presents a roadmap for examining the phenomenon of monarchy in Asia, which we conceive as a pluralist institution in a twofold manner. First, many monarchies discharge a wide range of roles and responsibilities ranging from the symbolic to the religious to the legal-political. These varied functions can be usefully captured under the notion of constitutional guardianship, and call for intersectional analysis. Second, it is common for monarchies to have metamorphosed from being purely endogenous institutions to becoming ones embedded in a scheme of limited, constitutional government under the influence of ideas from elsewhere. Monarchies should accordingly be viewed as a form of legal métissage, viz. a braiding of local and extraneous ideas, practices, and rules. In this sense, a law-and-society approach is more likely to reveal the nature of monarchies than a strictly legal-doctrinal approach, although some of the latter is needed to fully appreciate the former's significance.